2022
DOI: 10.3390/cancers15010126
|View full text |Cite
|
Sign up to set email alerts
|

Current Biological, Pathological and Clinical Landscape of HER2-Low Breast Cancer

Abstract: HER2-low breast cancer (BC) is a newly defined subset of HER2-negative BC that has HER2 immunohistochemical (IHC) score of 1+ or score of 2+/in situ hybridization (ISH) negative phenotype. Recent clinical trials have demonstrated significant clinical benefits of novel HER2 directing antibody-drug conjugates (ADCs) in treating this group of tumors. Trastuzumab-deruxtecan (T-Dxd), a HER2-directing ADC was recently approved by the U.S. Food and Drug Administration as the first targeted therapy to treat HER2-low B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 80 publications
0
16
1
2
Order By: Relevance
“…Previous studies conducted in large series of primary BCs reported on higher ERα/PgR expression in HER2-low as compared to HER2-0 BCs 12 . The fact that we did not observe such association may derive from the lower number of patients included in our study, or by different methods to evaluate ERα/PgR expression across different studies.…”
mentioning
confidence: 87%
“…Previous studies conducted in large series of primary BCs reported on higher ERα/PgR expression in HER2-low as compared to HER2-0 BCs 12 . The fact that we did not observe such association may derive from the lower number of patients included in our study, or by different methods to evaluate ERα/PgR expression across different studies.…”
mentioning
confidence: 87%
“…Additionally, the choice of staining methodology, particularly antigen retrieval, and the availability of different antibody clones with varying specificity can also impact the accuracy and reproducibility of results ( Schrohl et al, 2011 ; Zhang et al, 2021 ). The VENTANA PATHWAY anti-HER2/neu (4B5) rabbit monoclonal primary antibody has been approved by the FDA as the first companion diagnostic test to identify HER2-low mBC patients for trastuzumab deruxtecan (T-DXd) targeted therapy ( Zhang and Peng, 2022 ). However, assessing the reliability of other commonly used HER2 IHC testing methods is still pending ( Zhang and Peng, 2022 ).…”
Section: Current Challenges: How Far From the Perfect Test?mentioning
confidence: 99%
“…The VENTANA PATHWAY anti-HER2/neu (4B5) rabbit monoclonal primary antibody has been approved by the FDA as the first companion diagnostic test to identify HER2-low mBC patients for trastuzumab deruxtecan (T-DXd) targeted therapy ( Zhang and Peng, 2022 ). However, assessing the reliability of other commonly used HER2 IHC testing methods is still pending ( Zhang and Peng, 2022 ). Repeating the test for equivocal results may help to exclude technical problems, however, it does not always lead to a definitive result.…”
Section: Current Challenges: How Far From the Perfect Test?mentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of antibody‐drug conjugates (ADCs), HER2‐low expression has been proposed as an emerging subtype based on its potential benefit from anti‐HER2 ADCs 5,8 . Recent clinical studies suggested that HER2‐low expression breast cancers have unique clinicobiological features, different pathological complete rates (pCR) and prognoses compared with HER2‐zero expression 9–11 . In this context, accurate evaluation of HER2 status is critical for the appropriate use of HER2‐targeted therapies, which is not only specific to the distinction of HER2‐positive from HER2‐negative breast cancers but also applicable to the distinction of HER2‐low from HER2‐negative breast cancers.…”
mentioning
confidence: 99%